A Crystal Engineering Approach for the Design of High-Performing, Low Sensitivity, Nitrogen-Rich Energetic Salts - Herweyer, Darren (Université d'Ottawa / University of Ottawa, 2022)
Nitrogen-rich energetic materials (EMs) are characterized by their typically high values for heat-of-formation as well as the environmental benefit associated with the production of nitrogen gas upon detonation. This makes them the most likely class of materials to replace currently used explosives such as lead azide (LA), 2,4,6-trinitrotoluene (TNT), and 1,3,5-trinitro-1,3,5-triazacyclohexane (RDX). The sensitivity of EMs to mechanical stimuli such as impact and friction is governed primarily by the packing arrangement, as observed in the crystal structure. For this reason, crystal engineering is the most effective tool to achieve low sensitivity, high-performing EMs. In Chapter 2 the pH-dependent formation of two different dihydrazinyl tetrazine/azobistetrazolate salts was explored. These materials have high calculated detonation parameters and are expected to have large differences in sensitivity based on the different packing arrangements adopted. In Chapter 3, azobistetrazolate was substituted for a series of more thermally stable anions for the creation of a family of dihydrazinyltetrazine-based secondary explosives. The use of oxalyldihydrazide (ODH) as an energetic cation was explored in Chapter 4, where the selective formation of both singly and doubly protonated versions of ODH allowed for the creation of both 1:1 and 2:1 energetic salts.
Keywords: Energetic; Explosive; Nitrogen